TWO STAGE ON OFF KEYING CLASS A RF POWER AMPLIFIER IN 0.18μm CMOS TECHNOLOGY - Senadeera, P.M.; Xie, Zhijian; Dogan, Numan S. (International Journal of Research -GRANTHAALAYAH, 2020)
A novel architecture for the On Off Keying (OOK) modulator with high gain and high data rate power amplifier (PA) operating at 11.6 GHz IBM 0.18-µm RF CMOS technology is presented for a X-band passive RFID tag. Currently used low frequency switching techniques such as multiplexers were not functioning in the high frequency X-band architectures. In this novel approach OOK modulator with power amplifier, a CMOS switch was used to transmit ‘1’ and ‘0’ coming from the digital signal unlike in the existing low frequency architectures. Both the load and driver in this proposed PA were class A operation supplied by a single ended 1.83V source. The important design considerations include output power, 1 dB compression point and linearity. The fabricated results of the amplifier have a 1 dB compression point of 1.2 dBm and input power of 5.19 dBm at 9.2 GHz.